Nasogastric versus Orogastric Bolus Tube Feeding in Preterm Infants: Pilot Randomized Clinical Trial - Badran, Ahmed Tawfik; Hashish, Menna; Ali, Alaa; Shokeir, Mohamed; Shabaan, Abd (American Journal of Perinatology, 2020)
Objective According to the most recent metanalysis, the best way to establish safe enteral feeding in preterm babies using nasogastric or orogastric tubes is still not well understood. This study aimed to determine the effects of bolus nasal tubes versus bolus orogastric tubes on the time required to reach full enteral feeding in preterm infants, as well as to compare the incidence rates of adverse events including nonintentional removal or displacement of the feeding tube, aspiration pneumonia/pneumonitis, apnea, necrotizing enterocolitis, gastric residual, and growth parameters between the studied cohort of preterm infants.Study Design We conducted an unblinded pilot randomized clinical trial on hemodynamically stable preterm infants (>28 weeks) recruited from level 2 neonatal intensive care unit at Mansoura University Children's Hospital from June 2015 to May 2017.Results Our study included 98 stable preterm infants with mean gestational age (orogastric group: 33.27 ± 1.08, nasogastric group: 33.32 ± 1.57) and mean birthweight (orogastric group: 1,753.3 ± 414.51, nasogastric group: 1,859.6 ± 307.05). Preterm infants who were fed via bolus nasogastric tube achieved full enteral feeding in a significantly shorter duration compared with the infants fed via bolus orogastric tube. The incidence rates of aspiration and feeding tube displacement were significantly higher in the bolus orogastric tube group compared with the bolus nasogastric tube group. There was no difference in the incidence rates of apnea, necrotizing enterocolitis, bradycardia, oxygen desaturation, and gastric residual in both groups.Conclusion Preterm infants without any respiratory support receiving bolus nasogastric tube feeding achieved full enteral feeding significantly sooner than those receiving bolus orogastric tube feeding. Additionally, bolus nasogastric tube feeding had a lower incidence of aspiration, tube displacement, and the infants regained birthweight more quickly than those receiving orogastric tube feeding.Key Points
Keywords: preterm baby; enteral feeding; nasogastric tubes; orogastric tubes; growth; adverse effects